Bihar Third Five Year-Year Plan Progress Report for the Period Ending June, 1964 - Planning Commission (Planning Commission, 1964)
Progress of Expenditure Under the Major Heads, Sectorwise Progress of Expenditure, Schemewise Progress, Agriculture Programme, Co-Operation Community Development and Gram Panchayat, Irrigation and Flood Control, Industries and Mining, Transport and Communications, Social Services.
Bihar